posted by kelly on .
can somebody help me out? am I doing this right? using the elimination method.
y = 3x + 2
We have the solution for y so we use this to solve
2 (3x + 2) – 6x = 4
6x + 4 – 6x = 4
0x +4 = 4
Subtract 4 from both sides
Now we use 0 for the x value in equation one
y = 3x + 2....(1)
If you multiply (1) by 2 and transpose terms, you get equation (2).
This means that there is an infinite sets of solutions based on any value of t:
Geometrically the system represents two lines that are coincident, hence an infinite set of solutions.